Synthesis and Characterization of CeGdZn-Ferrite Nanoparticles as Magnetic Hyperthermia Application Agents - Saleh S. Hayek (Advances in Materials Science and Engineering)
This study focuses on the synthesis and characterization of a magnetic nanomaterial used in magnetic hyperthermia. Cerium gadolinium zinc-iron (CeGdZnFe) magnetic nanoparticles were synthesized by a coprecipitation method for application as magnetic hyperthermia agents. Determination of phase purity and their identification was achieved by X-ray diffraction studies using a Phillips powder diffractometer with Cu Kα radiation. Typical TEM micrographs of the dispersion of CeGdZn-ferrite nanoparticles and CeGdZn-ferrite PEG-encapsulated nanoparticles in ethanol deposited over a Cu grid were taken as part of the characterization techniques to be used for newly developed materials. It was then fitted by a Gaussian distribution with mean diameter dm ±1.0 nm. The investigation of magnetic properties showed that adjusting, Gd and Zn contributes to the nanoparticles added to the adjustment of all magnetic properties of CeGdZnFe.